MUSE narrow field mode observations of the central kinematics of M15. Issue 2 (27th February 2021) - Usher, Christopher; Kamann, Sebastian; Gieles, Mark; Hénault-Brunet, Vincent; Dalessandro, Emanuele; Balbinot, Eduardo; Sollima, Antonio
ABSTRACT: We present observations of the stellar kinematics of the centre of the core collapsed globular cluster M15 obtained with the MUSE integral field spectrograph on the Very Large Telescope operating in narrow field mode. Thanks to the use of adaptive optics, we obtain a spatial resolution of 0.1 arcsec and are able to reliably measure the radial velocities of 864 stars within 8 arcsec of the centre of M15, thus providing the largest sample of radial velocities ever obtained for the innermost regions of this system. Combined with previous observations of M15 using MUSE in wide field mode and literature data, we find that the central kinematics of M15 are complex with the rotation axis of the core of M15 offset from the rotation axis of the bulk of the cluster. While this complexity has been suggested by previous work, we confirm it at higher significance and in more detail.